2002
DOI: 10.1046/j.1420-9101.2002.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism in Caulerpa taxifolia (Ulvophyceae) chloroplast DNA revealed by a PCR-based assay of the invasive Mediterranean strain

Abstract: An invasive, cold-tolerant strain of the tropical green alga Caulerpa taxifolia was introduced recently in the Mediterranean Sea and along the Californian coast. We screened 50 aquarium and open-sea C. taxifolia specimens for the presence ⁄ absence of an intron located in the rbcL gene of chloroplast DNA. We also reanalysed a total of 229 sequences of the Internal Transcribed Spacer (ITS) of ribosomal DNA, combining previously published sequences from different studies with 68 new sequences to complement rbcL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Amplification success was low in general, a result that might be expected if these taxa represent complexes of cryptic species, as has been shown in C. racemosa (Famà et al 2002) and hypothesized for C. taxifolia (Meusnier et al 2002 Disclaimer This report was prepared as an account of work sponsored by an agency of the US Government. Neither the US Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights.…”
Section: Resultsmentioning
confidence: 99%
“…Amplification success was low in general, a result that might be expected if these taxa represent complexes of cryptic species, as has been shown in C. racemosa (Famà et al 2002) and hypothesized for C. taxifolia (Meusnier et al 2002 Disclaimer This report was prepared as an account of work sponsored by an agency of the US Government. Neither the US Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights.…”
Section: Resultsmentioning
confidence: 99%
“…conclusions Although molecular tools have been used to investigate invasive algae in the North Atlantic (Chualáin et al 2004, Provan et al 2005 and Mediterranean Sea (Famà et al 2002, Meusnier et al 2002, Piazza and Cinelli 2003, this study is the first to examine the population genetics and biogeography of an alien seaweed in Hawai'i. Our analyses indicate a surprising amount of within-and among-population variation based on ISSR markers, but DNA sequence analyses of the mitochondrial cox 2-3 spacer and a fragment of the nuclear ribosomal large subunit gene failed to reveal any variation.…”
Section: Management Recommendationsmentioning
confidence: 89%
“…In temperate latitudes, DNA sequencing and fragment techniques have been used to investigate invasions of green and red seaweeds. These molecular tools have been used to determine the possible geographic sources and the genetic diversity of notable invasive algae such as Caulerpa taxifolia, Grateloupia doryphora, and Asparagopsis taxiformis (Famà et al 2002, Marston and VillalardBohnsack 2002, Chualáin et al 2004). In the study reported here, DNA sequence analyses of a region of the nuclear ribosomal large subunit gene and the mitochondrial cox 2-3 spacer region, and Inter-Simple Sequence Repeats (ISSRs) were used to investigate the population structure of A. spicifera throughout the main Hawaiian Islands.…”
mentioning
confidence: 99%
“…More variable markers such as the internally transcribed spacers of the rRNA cistron (ITS) might be useful in detecting even more hidden diversity, despite potential problems concerning intraindividual variation in the ITS region (Famà et al. , ). Generally, the analysis of multiple loci in the Cladophorales is problematic due to amplification problems of organellar DNA (as yet it has been impossible to amplify chloroplast or mitochondrial DNA, e.g., Furumoto , Verbruggen et al.…”
Section: Discussionmentioning
confidence: 99%